Bases of turning and exposure- An analytical study - Akour, Hajar Khalifa (Journal of Humanities & Social Sciences, 2018)
This research aimed to clarify the meaning of the rules of turning and exposure and exposure، and the legalization of them، with the identification of the point of legitimate estimate، and knowledge of the impact of jurisprudence by striking some examples of jurisprudence on them، and the study of appreciation of the scholars A and its references to the fundamentals of Islamic jurisprudence and jurisprudence، the researcher followed the method inductive and analytical، And reached the researcher that the estimates of legitimacy is an important approach in the Islamic jurisprudence، and the diligent must take into account the tasks of things، and the turn of the sentences، before the issuance of the legitimacy.
Keywords: legal estimations; legal capabilities; inflection; exposure; outcomes; jurisprudential rules